Ciprofloxacin therapy for Mediterranean spotted fever. - Raoult, D (1986)
We report the treatment of five patients with Mediterranean spotted fever with the antimicrobial agent ciprofloxacin. The treatment was administered intravenously for 2 days and then perorally for 8 days. All five patients were cured. These preliminary data seem to correlate with the in vitro activity of ciprofloxacin against Rickettsia conorii.